Amelioration Peat With Various Industrial Waste on Growth and Results Two Varieties of Maize (Zea mays L.) - Marlina Marlina; Nelvia Nelvia; Armaini Armaini (Jurnal Agroteknologi, 2017)
This study aims to get ameliorant formulations of various industrial wastes most suitable for the growth and yield of maize varieties Earth-3 and NK-212 in peatland, research design using a split plot design with 12 combination and each treatment was repeated 3 times. The main plot of treatment consists of: (V1): Varieties of Earth-3, (V2): Varieties of NK-212. Treatment subplot, which consists of six formulations ameliorant, namely: F1 (60% TKKS + 20% ATKS + 10% dregs + 10% fly ash), F2 (60% TKKS + 10% ATKS + 20% dregs + 10% fly ash ), F3 (60% TKKS + 10% ATKS + 10% dregs + 20% fly ash), F4 (40% TKKS + 30% ATKS + 10% dregs + 20% fly ash), F5 (40% TKKS + 20% ATKS dregs + 30% + 10% fly ash) and F6 (40% + 10% TKKS ATKS dregs + 20% + 30% fly ash). The data obtained were statistically analyzed using analysis of variance (ANOVA) followed by HSD test at a rate of 5%.The results showed that the peat soil improvement ameliorant consists of various formulations, is 40-60% TKKS, ATKS 10-30%, 10-30% and 10-30% fly ash Dregs, giving real effect to the varieties and formulations ameliorant. Varieties significantly affect a male flowers and female flowers. Formulation ameliorant significant effect on plant height and timing of male flowers and female flowers. Interactions both provide the same effect on all observed variables, and results from the production of the resulting show, cob was formed to produce cob big and long, the number of lines of neatly arranged and the seed is fully charged and the skin covering the cob well (± 98%) is in conformity with description. This is because the availability of nutrients that keep running from ameliorant provided, so that the nutrients are available to be fairly balanced.Varieties of Earth-3 with formulations F6, better used for peat because varieties of proven Earth-3 and F6 formulations were able to accelerate the emergence of male flowers and female flowers, thus spurring the generative plant growth, by accelerating the maturation of seeds so as to accelerate the harvest.